ISTISHHÂB SEBAGAI TEORI HUKUM ISLAM SEBUAH TINJAUAN HISTORIS - Muhammad Taufiq (Indonesian Journal of Law and Islamic Law (IJLIL), 2019)
Although in substance Istishhâb has existed since the era of the Prophet, Istishhâb is still included in the category of Islamic legal propositions that are mukhtalaf fîh (there are differences among scholars). The construction of the new Istishhâb theory began in the fifth hijri adad in a clear and detailed manner. This paper wants to further discuss Istishhâb as a theory of Islamic law, from a historical perspective. From this point of view, it can later be concluded whether Istishhâb can be considered as a theory of Islamic law or just a method of Islamic law istinbath.